Medical magnesium alloy and preparation method and application thereof

By adding Er/Gd/Ag nanomaterials and graphene nanosheets to medical magnesium alloys and adopting multi-stage composite treatment process, the problem of corrosion and dissolution of medical magnesium alloys in body fluid environments is solved, and its corrosion resistance and fatigue performance and service life are significantly improved.

CN119736533APending Publication Date: 2025-04-01NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940711.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Medical magnesium alloys are prone to corrosion and dissolution in body fluid environments, resulting in corrosion fatigue damage, and the failure areas and service life are difficult to predict, which poses safety hazards.

Method used

The Er/Gd/Ag nanomaterial and graphene nanosheets were used to synergistically add Er/Gd/Ag nanomaterials and graphene nanosheets, and through multi-stage composite treatment processes such as vacuum smelting, equal diameter angle extrusion, warm rolling and ultrasonic surface rolling, medical magnesium alloys with excellent mechanical properties and corrosion fatigue resistance were prepared.

Benefits of technology

It significantly improves the corrosion fatigue resistance of medical magnesium alloys, extends its service life, avoids stratified cracking and sudden fracture during use, and enhances its safety and reliability in clinical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736533A_ABST
    Figure CN119736533A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium alloy plastic processing, and discloses a medical magnesium alloy and a preparation method and application thereof. The medical magnesium alloy is prepared from the following chemical components in percentage by mass: 1.83 percent to 2.10 percent of Er, 6.10 percent to 8.40 percent of Gd, 0.15 percent to 0.25 percent of Ag, 0.03 percent to 0.25 percent of graphene nanosheets GNPs, 1.70 percent to 3.35 percent of Zn and the balance of Mg. According to the invention, on the basis of realizing excellent mechanical properties through synergistic addition of rare earth elements Er / Gd and nano particles GNPs, by virtue of crystal face characteristics of a heavy rare earth phase and a strong lattice distortion relationship with a magnesium-based interface, a slip step / slip line in a deformation area is obviously changed, and crack initiation and propagation penetration of a corrosion fatigue tip are inhibited. In addition, in the using process of the medical magnesium alloy, the phenomena of layering, cracking and sudden breaking can be avoided, and the corrosion fatigue service life of the medical magnesium alloy is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy plastic processing, and in particular to a medical magnesium alloy and a preparation method and application thereof. Background Art

[0002] Compared with traditional inert human implants such as stainless steel, titanium alloys, cobalt / nickel-based alloys, and bioceramics, magnesium alloys have shown great application potential in the medical field due to their good biocompatibility, spontaneous degradation, and elastic modulus matching that of adult bones. They are known as "contemporary revolutionary medical metal materials." As large-scale bone repair / fixation implants, magnesium alloys can minimize stress shielding effects, accelerate cell proliferation and differentiation, induce bone load transfer, and enhance new bone remodeling effects. As small, thin-walled stents, magnesium alloys can achieve radial support and reduce vascular restenosis rates in coronary vascular / urinary system stents, and maintain normal dynamic blood circulation in the human body. The Mg released during degradation during service 2+ Can participate in the synthesis and metabolic reactions of all functional proteases in the human body, redundant Mg 2+ It can be excreted from the body through metabolism or urine and will not cause accumulation of metal elements in the human body, showing great clinical implantation advantages.

[0003] However, magnesium alloys are very susceptible to corrosion and dissolution in a wet environment (the standard electrode potential is low, -2.73V). Especially in a complex body fluid environment, medical magnesium alloys are not only subjected to body fluid erosion / abrasion, but also to corrosion fatigue damage caused by nonlinear mechanical load-electrochemical interaction. Compared with static corrosion and stress corrosion, the degree of damage is stronger and the form of damage is more dangerous. In addition, the failure site and service life of the alloy are also extremely difficult to predict. It may even cause clinical problems such as bone tissue necrosis, puncture of blood vessels, and damage to surrounding tissues, seriously endangering the patient's life safety. Summary of the invention

[0004] The purpose of the present invention is to provide a medical magnesium alloy and a preparation method and application thereof, so as to solve the problem that the existing medical magnesium alloy is very easy to corrode and dissolve in the body fluid environment.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a medical magnesium alloy, comprising the following chemical components in mass percentage: Er: 1.83-2.10%, Gd: 6.10-8.40%, Ag: 0.15-0.25%, graphene nanosheets GNPs: 0.03-0.25%, Zn: 1.70-3.35%, and the balance is Mg.

[0007] The present invention also provides a method for preparing a medical magnesium alloy, comprising the following steps:

[0008] S1. According to the mass percentage of chemical components, Mg alloy, Zn alloy, Ag, GNPs sheet material, magnesium-erbium alloy ingot and magnesium-gadolinium master alloy are mixed, vacuum smelted and cast to obtain alloy ingot;

[0009] S2, performing equal-channel angular extrusion deformation treatment on the alloy ingot in step S1 to obtain an initial extruded ingot;

[0010] S3, performing warm rolling deformation treatment on the initial extruded ingot in step S2 to obtain an intermediate transition rolled ingot;

[0011] S4, performing ultrasonic surface rolling treatment on the intermediate transition rolling ingot described in step S3 to obtain a medical magnesium alloy.

[0012] Preferably, in the preparation method, in step S1, the vacuum melting conditions include: the atmosphere is argon, the vacuum degree is 120-150 Pa, the temperature is 720-750°C, and the time is 10-12 min; in step S1, the casting conditions include: the temperature is 680-710°C, and the casting rate is 20-25 mm / min.

[0013] Preferably, in the preparation method, in step S1, a slow cooling treatment is further included after the casting, and the cooling rate of the slow cooling treatment is 1 to 3°C / s.

[0014] Preferably, in the preparation method, in step S2, the conditions of the equal-channel angular extrusion deformation treatment include: an extrusion angle of 120 to 150°, a mold temperature of 470 to 480°C, an extrusion temperature of 440 to 460°C, and 6 to 8 extrusion passes; annealing treatment is performed between every two passes, the annealing treatment temperature is 390 to 420°C, and the annealing treatment time is 10 to 13 minutes.

[0015] Preferably, in the preparation method, in step S2, the alloy ingot further includes a secondary variable temperature homogenization heat treatment before the equal channel angular extrusion deformation treatment; the conditions of the secondary variable temperature homogenization heat treatment include: the temperature of the first stage heat treatment is 320-400°C, the holding time of the first stage heat treatment is 4-6h, the temperature of the second stage heat treatment is 260-280°C, the holding time of the second stage heat treatment is 4-6h, and the vacuum degree is less than 1×10 -2 Pa.

[0016] Preferably, in the preparation method, in step S3, the conditions of the warm rolling deformation treatment include: a rolling rate of 40 to 60 mm / s, a rolling temperature of 360 to 400°C, 5 to 7 rolling passes, a first rolling reduction of 15 to 20%, and a remaining rolling reduction of ≤8 to 10%; annealing treatment is performed between every two passes, the annealing treatment temperature is 360 to 380°C, and the annealing treatment time is 10 to 15 min.

[0017] Preferably, in the preparation method, in step S3, the initial extruded ingot further includes stress relief annealing before the warm rolling deformation treatment; the conditions of the stress relief annealing include: temperature of 250-280° C., time of 90-110 min.

[0018] Preferably, in the preparation method, in step S4, the conditions of the ultrasonic surface rolling treatment include: the diameter of the polishing ball is 8 to 12 mm, the rolling ultrasonic frequency is 20 to 30 Hz, the ultrasonic amplitude is 6 to 8 μm, the feed rate is 20 to 40 mm / min, the static pressure load is 280 to 350 N, the spindle speed is 180 to 200 rpm, and the number of double-sided rolling is 2 to 4 times; during the ultrasonic surface rolling treatment, liquid nitrogen spray cooling is performed every 2 minutes.

[0019] The present invention also provides an application of the medical magnesium alloy in preparing a medical magnesium alloy sheet.

[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) In the scheme of the present invention, the synergistic addition of rare earth elements Er / Gd and nano GPNs sheets can significantly increase the non-uniform nucleation rate of the alloy liquid, reduce the solute segregation degree in the micro-region on the basis of achieving excellent mechanical properties, and weaken the driving force of galvanic corrosion. Moreover, the insoluble deposited salt substance Gd(OH)3 / Er(OH)3 formed by the hydrolysis of the rare earth elements Gd / Er further enhances the integrity and density of the film layer on the surface of the substrate, and slows down the reaction rate and reaction exchange density of the corrosion current between the solution and the substrate.

[0022] (2) The Er / Ag regulating elements in the present invention significantly enhance the adhesion of the alloy surface film and weaken the adsorption and diffusion behavior of corrosive ions. In addition, the multi-stage aging precipitation of the Er / Ag-containing second phase enhances the matrix lattice distortion, delays the formation of surface slip planes and slip bands, enhances the stability and density of the surface passivation film in the plastic zone and toughness zone at the crack tip, and jointly inhibits the initiation and extension of corrosion fatigue tip cracks.

[0023] (3) The present invention not only makes up for the deficiency of single deformation through the integrated composite treatment process of equal-diameter angular extrusion / warm rolling and surface ultrasonic rolling, but also effectively obtains uniform and fine matrix structure and gradient nano-structured surface structure. High stress concentration causes the atomic distance to become smaller and forms a dense and stable oxide film, inhibits the rupture of the oxide film layer, helps to reduce the surface roughness, and thus enhances the corrosion fatigue resistance of medical magnesium alloys. In addition, the composite treatment process can also enhance the surface grain boundary density, promote surface lattice torsion and weaken the basal surface texture, promote the simultaneous activation and start of the basal surface / non-basal surface slip system, and thus significantly improve the corrosion fatigue resistance of medical magnesium alloys, obtain medical magnesium alloys with high ultimate strength and excellent corrosion fatigue resistance, avoid delamination cracking and sudden breakage during use, and greatly extend the corrosion fatigue service life of medical magnesium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0025] Figure 1 This is the SEM morphology of the surface film layer of the alloy obtained in Example 1 after immersion for 7 days;

[0026] Figure 2 This is the SEM morphology of the surface film layer of the alloy obtained in Example 2 after immersion for 7 days;

[0027] Figure 3 This is the SEM morphology of the surface film layer of the alloy obtained in Example 3 after immersion for 7 days;

[0028] Figure 4 This is the SEM microstructure of the alloy obtained in Example 3. DETAILED DESCRIPTION

[0029] The invention provides a medical magnesium alloy, comprising the following chemical components in mass percentage: Er: 1.83-2.10%, Gd: 6.10-8.40%, Ag: 0.15-0.25%, graphene nanosheets GNPs: 0.03-0.25%, Zn: 1.70-3.35%, and the balance is Mg.

[0030] In the present invention, the mass percentage of Er is preferably 1.86 to 2.05%, more preferably 1.92 to 2.00%, and even more preferably 1.95 to 1.98%.

[0031] In the present invention, the mass percentage of Gd is preferably 6.34 to 8.00%, more preferably 6.62 to 7.84%, and even more preferably 6.80 to 7.20%.

[0032] In the present invention, the mass percentage of Ag is preferably 0.17 to 0.23%, more preferably 0.19 to 0.21%, and even more preferably 0.20 to 0.21%.

[0033] In the present invention, the mass percentage of graphene nanosheets GNPs is preferably 0.10 to 0.22%, more preferably 0.12 to 0.20%, and more preferably 0.16 to 0.19%.

[0034] In the present invention, the mass percentage of Zn is preferably 1.92 to 3.17%, more preferably 2.05 to 3.00%, and even more preferably 2.45 to 2.72%.

[0035] The present invention also provides a method for preparing a medical magnesium alloy, comprising the following steps:

[0036] S1. According to the mass percentage of chemical components, Mg alloy, Zn alloy, Ag, GNPs sheet material, magnesium-erbium alloy ingot and magnesium-gadolinium master alloy are mixed, vacuum smelted and cast to obtain alloy ingot;

[0037] S2, performing equal-channel angular extrusion deformation treatment on the alloy ingot in step S1 to obtain an initial extruded ingot;

[0038] S3, performing warm rolling deformation treatment on the initial extruded ingot in step S2 to obtain an intermediate transition rolled ingot;

[0039] S4, performing ultrasonic surface rolling treatment on the intermediate transition rolling ingot described in step S3 to obtain a medical magnesium alloy.

[0040] In the present invention, in step S1, the purity of the magnesium alloy is preferably ≥99.95%; the purity of the Zn alloy is preferably ≥99.99%; the purity of the Ag is preferably ≥99.94%; the purity of the GNPs sheet material is preferably ≥99.5%; the purity of the magnesium-erbium alloy ingot (Mg-20Er) is preferably ≥99.93%; the purity of the magnesium-gadolinium master alloy (Mg-20%Gd) is preferably ≥99.92%.

[0041] In the present invention, in step S1, before the vacuum smelting is performed, it is preferred to include: pre-smelting with a high-purity magnesium ingot to remove impurities in the furnace; and then vacuuming.

[0042] In the present invention, the volume for pre-smelting is preferably ≥ 1 / 5 of the volume of the furnace.

[0043] In the present invention, the vacuuming preferably reaches 10 -3 ~10 -4 Pa.

[0044] In the present invention, in step S1, the conditions for vacuum melting include: the atmosphere is preferably argon; the vacuum degree is preferably 120-150 Pa, more preferably 120-130 Pa, more preferably 120 Pa; the temperature is preferably 720-750°C, more preferably 735-750°C, more preferably 750°C; the time is preferably 10-12 min, more preferably 10-11 min, more preferably 10 min.

[0045] In the present invention, in step S1, the casting method is preferably the whole-body tilting casting of the crucible in the furnace.

[0046] In the present invention, in step S1, the casting mold is preferably a graphite mold with a small bottom diameter and a large opening. Specifically in the embodiment of the present invention, the conditions of the graphite mold include: the wall thickness is preferably 20-25 mm, more preferably 20-23 mm, and more preferably 20 mm; the bottom thickness is preferably 8-10 mm, more preferably 9-10 mm, and more preferably 10 mm; the diameter is preferably 10-18 mm, more preferably 15-18 mm, and more preferably 15 mm.

[0047] In the present invention, in step S1, the mold is preheated before the casting, and the preheating temperature is preferably 220-240°C, more preferably 220-230°C, and more preferably 230°C.

[0048] In the present invention, in step S1, the casting conditions include: the temperature is preferably 680-710°C, more preferably 695-710°C, and more preferably 710°C; the casting rate is preferably 20-25 mm / min, more preferably 20-23 mm / min, and more preferably 20 mm / min.

[0049] In the present invention, in step S1, a slow cooling treatment is further included after the casting; the slow cooling treatment is preferably performed after the cast alloy liquid has been stationary for 15 minutes.

[0050] In the present invention, the cooling rate of the slow cooling treatment is preferably 1 to 3°C / s, more preferably 1 to 2°C / s, and even more preferably 1°C / s.

[0051] In the present invention, in step S2, the alloy ingot preferably further includes a secondary variable temperature homogenization heat treatment before the equal channel angular extrusion deformation treatment.

[0052] In the present invention, the conditions of the two-stage variable temperature homogenization heat treatment include: the temperature of the first stage heat treatment is preferably 320-400°C, more preferably 360-400°C, more preferably 360°C; the holding time of the first stage heat treatment is preferably 4-6h, more preferably 4-5h, more preferably 4h; the temperature of the second stage heat treatment is preferably 260-280°C, more preferably 270-280°C, more preferably 280°C; the holding time of the second stage heat treatment is preferably 4-6h, more preferably 4-5h, more preferably 4h; the vacuum degree is <1×10 -2 Pa.

[0053] In the present invention, the cooling method of the two-stage variable temperature homogenization heat treatment is preferably: water cooling, followed by air cooling and drying.

[0054] In the present invention, between the secondary variable temperature homogenization heat treatment and the equal channel angular extrusion deformation treatment, it is preferred that the process further includes: applying lubricating oil to the surface of the alloy ingot.

[0055] In the present invention, in step S2, the conditions of the equal-channel angular extrusion deformation treatment include: the extrusion angle is preferably 120-150°, more preferably 130-140°, and more preferably 130°; the mold temperature is preferably 470-480°C, more preferably 475-480°C, and more preferably 480°C; the extrusion temperature is preferably 440-460°C, more preferably 450-460°C, and more preferably 450°C; the extrusion passes are preferably 6-8 passes, more preferably 7-8 passes, and more preferably 7 passes.

[0056] In the present invention, in step S2, annealing treatment is preferably performed between every two passes of the equal-channel angular extrusion deformation treatment; the temperature of the annealing treatment is preferably 390-420°C, more preferably 400-420°C, and more preferably 420°C; the time of the annealing treatment is preferably 10-13 min, more preferably 10-12 min, and more preferably 12 min.

[0057] In the present invention, in step S2, after the equal channel angular extrusion deformation treatment is completed, it is preferred to further include: water cooling, the purpose of which is to prevent grain growth and retain its deformed structure.

[0058] In the present invention, in step S3, the initial extruded ingot is preferably subjected to stress relief annealing before being subjected to warm rolling deformation treatment.

[0059] In the present invention, the stress relief annealing conditions include: the temperature is preferably 250-280°C, more preferably 260-280°C, and more preferably 260°C; the time is preferably 90-110 min, more preferably 100-110 min, and more preferably 100 min.

[0060] In the present invention, after the stress relief annealing is completed, furnace cooling is preferably performed.

[0061] In the present invention, in step S3, the conditions of the warm rolling deformation treatment include: the rolling rate is preferably 40-60 mm / s, more preferably 40-50 mm / s, and more preferably 50 mm / s; the rolling temperature is preferably 360-400°C, more preferably 380-400°C, and more preferably 380°C; the rolling passes are preferably 5-7 passes, more preferably 6-7 passes, and more preferably 6 passes; the reduction in the first rolling pass is preferably 15-20%, more preferably 15-18%, and more preferably 15%; the reduction in the remaining rolling passes is preferably ≤8-10%, further preferably ≤8-9%, and more preferably ≤8%.

[0062] In the present invention, in step S3, annealing treatment is preferably performed between every two passes of the warm rolling deformation treatment; the temperature of the annealing treatment is preferably 360-380°C, more preferably 370-380°C, and more preferably 375°C; the time of the annealing treatment is preferably 10-15min, more preferably 12-15min, and more preferably 15min.

[0063] In the present invention, in step S3, water quenching is preferably performed immediately after the warm rolling deformation treatment is completed.

[0064] In the present invention, in step S4, the intermediate transition rolling ingot is preferably subjected to ultrasonic surface rolling treatment and further includes: using sandpaper to grind both sides in the rolling direction. The specification of the sandpaper is preferably 1000# to 2000#, more preferably 1500# to 2000#, and more preferably 2000#. The grinding thickness is preferably 0.1 to 0.4 mm, more preferably 0.1 to 0.2 mm, and more preferably 0.1 mm.

[0065] In the present invention, in step S4, after the double-sided grinding, preferably lubricating oil is applied to the normal contact surface of the polished sample.

[0066] In the present invention, in step S4, the conditions of the ultrasonic surface rolling treatment include: the diameter of the polishing ball is preferably 8-12 mm, further preferably 10-12 mm, and more preferably 10 mm; the rolling ultrasonic frequency is preferably 20-30 Hz, further preferably 25-30 Hz, and more preferably 30 Hz; the ultrasonic amplitude is preferably 6-8 μm, further preferably 7-8 μm, and more preferably 8 μm; the feed rate is preferably 20-40 mm / min, further preferably 30-40 mm / min, and more preferably 30 mm / min; the static pressure load is preferably 280-350 N, further preferably 310-350 N, and more preferably 310 N; the spindle speed is preferably 180-200 rpm, further preferably 180-190 rpm, and more preferably 180 rpm; the number of double-sided rolling is preferably 2-4 times, further preferably 3-4 times, and more preferably 3 times.

[0067] In the present invention, in step S4, the material of the polishing ball subjected to ultrasonic surface rolling treatment is preferably WC / Co.

[0068] In the present invention, in step S4, during the ultrasonic surface rolling treatment, liquid nitrogen spray cooling is preferably performed every 2 minutes to prevent high-temperature oxidation and deterioration of the surface properties of the material.

[0069] The present invention also provides an application of the medical magnesium alloy in preparing a medical magnesium alloy sheet.

[0070] In the present invention, the application method is not limited, and any method known to those skilled in the art may be used.

[0071] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0072] Example 1

[0073] The present embodiment provides a medical magnesium alloy, comprising the following chemical components in mass percentage: Er: 1.83%, Gd: 6.10%, Ag: 0.15%, GNPs: 0.03%, Zn: 1.70%, and the balance is Mg.

[0074] The preparation method comprises the following steps:

[0075] S1. Use high-purity magnesium ingots for pre-melting in the furnace. The pre-melting volume is ≥ 1 / 5 of the furnace volume. Remove impurities in the furnace and then evacuate to 10 -3Pa; according to the mass percentage of chemical components, high-purity Mg alloy (purity ≥99.95%), high-purity Zn alloy (purity ≥99.99%), high-purity Ag thin strip (purity ≥99.94%), high-purity GNPs sheet (purity ≥99.5%), magnesium-erbium alloy ingot (purity ≥99.93%), magnesium-gadolinium master alloy (purity ≥99.92%) were weighed respectively, argon was introduced to make the vacuum degree reach 120Pa, and vacuum melting was carried out at 720℃ for 10min; then the crucible in the furnace was tilted as a whole, and the molten metal was cast into a preheated graphite mold with a small bottom diameter and a large opening (wall thickness of 20mm, bottom thickness of 8mm, diameter of 15mm, preheating temperature of 220℃), the casting temperature was 680℃, and the casting rate was 20mm / min; finally, the alloy liquid was slowly cooled after being stationary for 15min, and the cooling rate of the slow cooling was 1℃ / s to obtain an alloy ingot;

[0076] S2, the alloy ingot in step S1 is first subjected to a two-stage variable temperature homogenization heat treatment at 320°C / 4h and 280°C / 4h, and the vacuum degree is less than 1×10 -2 Pa, after the treatment is completed, water cooling and air cooling and drying treatment are carried out; lubricating oil is applied to the surface of the alloy ingot, and equal-diameter angular extrusion deformation treatment is carried out, the extrusion angle is 120°, the mold temperature is 470°C, the extrusion temperature is 440°C, and 6 extrusion passes are performed. Annealing treatment is performed between every two passes, the annealing temperature is 420°C, and the time is 10 minutes. After the end, water cooling is carried out to prevent grain growth and retain its deformation structure, and the initial extruded ingot is obtained;

[0077] S3, the initial extruded ingot in step S2 is first subjected to stress relief annealing at a temperature of 250°C and a time of 90 minutes, and then cooled in the furnace after the stress relief annealing is completed; then warm rolling deformation treatment is performed, the rolling rate is 40 mm / s, the rolling temperature is 360°C, and the rolling is performed for 5 times, the first rolling reduction is 15%, and the remaining rolling reduction is 8%, and annealing treatment is performed between every two passes, the annealing temperature is 380°C and the time is 10 minutes, and water quenching treatment is performed immediately after the warm rolling deformation treatment is completed to obtain an intermediate transition rolling ingot;

[0078] S4. The intermediate transition rolled ingot described in step S3 is first polished on both sides by 0.1 mm in the rolling direction with 1000# sandpaper, lubricating oil is applied to the normal contact surface of the polished sample, and then ultrasonic surface rolling treatment is performed. The diameter of the polishing ball is 8 mm, the material of the polishing ball is WC / Co, the rolling ultrasonic frequency is 20 Hz, the ultrasonic amplitude is 6 μm, the feed rate is 20 mm / min, the static pressure load is 280 N, the spindle speed is 180 rpm, and the double-sided rolling is performed twice. During the ultrasonic surface rolling treatment, liquid nitrogen spray cooling is performed every 2 minutes to prevent high-temperature oxidation and deterioration of the surface properties of the material, so as to obtain a medical magnesium alloy.

[0079] The corrosion fatigue performance of alloy plates was tested according to GB / T 20120.1-2006 "Corrosion of Metals and Alloys - Corrosion Fatigue Tests Part 1: Cyclic Failure Tests". Under the test conditions of stress ratio of -1, loading frequency of 5Hz, and stress amplitude of 80MPa, the fatigue life of medical magnesium alloy reached 0.8×10 5 Second-rate.

[0080] Figure 1 This is a SEM morphology of the surface film of the alloy obtained in Example 1 after being immersed in a simulated body fluid environment at 37±0.5℃ for 7 days. Figure 1 It can be seen that the relatively dense and complete product film layer on the alloy surface can effectively hinder the adsorption, diffusion and penetration of corrosive ions on the alloy surface, greatly increasing the corrosion resistance.

[0081] Example 2

[0082] The present embodiment provides a medical magnesium alloy, comprising the following chemical components in mass percentage: Er: 1.95%, Gd: 7.20%, Ag: 0.15%, GNPs: 0.16%, Zn: 2.05%, and the balance is Mg.

[0083] The preparation method comprises the following steps:

[0084] S1. Use high-purity magnesium ingots for pre-melting in the furnace. The pre-melting volume is ≥ 1 / 5 of the furnace volume. Remove impurities in the furnace and then evacuate to 10 -3 Pa; according to the mass percentage of the components, high-purity Mg alloy (purity ≥99.95%), high-purity Zn alloy (purity ≥99.99%), high-purity Ag thin strip (purity ≥99.94%), high-purity GNPs sheet (purity ≥99.5%), magnesium-erbium alloy ingot (purity ≥99.93%), and magnesium-gadolinium master alloy (purity ≥99.92%) were weighed respectively, and argon gas was introduced to make the vacuum degree reach 130Pa, and vacuum melting was carried out at 750°C for 10min; then the crucible in the furnace was tilted as a whole, and the molten metal was cast into a preheated graphite mold with a small bottom diameter and a large opening (wall thickness of 20mm, bottom thickness of 10mm, diameter of 15mm, preheating temperature of 230°C), the casting temperature was 710°C, and the casting rate was 25mm / min; finally, the alloy liquid was slowly cooled after being stationary for 15min, and the cooling rate of the slow cooling was 1°C / s to obtain an alloy ingot;

[0085] S2, then the alloy ingot in step S1 is first subjected to a two-stage variable temperature homogenization heat treatment at 360°C / 4h and 280°C / 4h, and the vacuum degree is less than 1×10 -2Pa, after the treatment is completed, water cooling and air cooling and drying treatment are carried out; lubricating oil is applied to the surface of the alloy ingot, and equal-diameter angular extrusion deformation treatment is carried out, the extrusion angle is 130°, the mold temperature is 480°C, the extrusion temperature is 450°C, and 7 extrusion passes are performed. Annealing treatment is performed between every two passes, the annealing temperature is 420°C, and the time is 10 minutes. After the end, water cooling is carried out to prevent grain growth and retain its deformation structure, and the initial extruded ingot is obtained;

[0086] S3, the initial extruded ingot in step S2 is first subjected to stress relief annealing at a temperature of 260°C and a time of 100 min, and then cooled in the furnace after the stress relief annealing is completed; then warm rolling deformation treatment is performed, the rolling rate is 50 mm / s, the rolling temperature is 380°C, and the rolling is performed for 6 passes, the first rolling reduction is 15%, and the remaining rolling reduction is 10%, and annealing treatment is performed between every two passes, the annealing temperature is 380°C and the time is 15 min, and water quenching is performed immediately after the warm rolling deformation treatment is completed to obtain an intermediate transition rolling ingot;

[0087] S4. The intermediate transition rolled ingot described in step S3 is first polished on both sides by 0.1 mm in the rolling direction with 2000# sandpaper, lubricating oil is applied to the normal contact surface of the polished sample, and then ultrasonic surface rolling treatment is performed. The diameter of the polishing ball is 10 mm, the material of the polishing ball is WC / Co, the rolling ultrasonic frequency is 25 Hz, the ultrasonic amplitude is 8 μm, the feed rate is 30 mm / min, the static pressure load is 310 N, the spindle speed is 180 rpm, and the double-sided rolling is performed 3 times. During the ultrasonic surface rolling treatment, liquid nitrogen spray cooling is performed every 2 minutes to prevent high-temperature oxidation and deterioration of the surface properties of the material, so as to obtain a medical magnesium alloy.

[0088] The corrosion fatigue performance of alloy plates was tested according to GB / T 20120.1-2006 "Corrosion of Metals and Alloys - Corrosion Fatigue Tests Part 1: Cyclic Failure Tests". Under the test conditions of stress ratio of -1, loading frequency of 5Hz, and stress amplitude of 80MPa, the fatigue life of medical magnesium alloy reached 1.2×10 5 Second-rate.

[0089] Figure 2 This is the SEM morphology of the surface film layer of the alloy obtained in Example 2 after being immersed in a simulated body fluid environment at 37±0.5℃ for 7 days. Compared with the cross-sectional corrosion profile obtained in Example 1, Figure 2 The cross-sectional profile is flatter, more complete and less defective, which can better inhibit the cathodic dynamics during the corrosion process, increase the polarization resistance of the alloy, and thus delay the corrosion process of the medical magnesium alloy in a simulated body fluid environment.

[0090] Example 3

[0091] The present embodiment provides a medical magnesium alloy, comprising the following chemical components in mass percentage: Er: 2.05%, Gd: 8.00%, Ag: 0.15%, GNPs: 0.20%, Zn: 3.00%, and the balance is Mg.

[0092] The preparation method comprises the following steps:

[0093] S1. Use high-purity magnesium ingots for pre-melting in the furnace. The pre-melting volume is ≥ 1 / 5 of the furnace volume. Remove impurities in the furnace and then evacuate to 10 -3 Pa; according to the mass percentage of chemical components, high-purity Mg alloy (purity ≥99.95%), high-purity Zn alloy (purity ≥99.99%), high-purity Ag thin strip (purity ≥99.94%), high-purity GNPs sheet (purity ≥99.5%), magnesium-erbium alloy ingot (purity ≥99.93%), magnesium-gadolinium master alloy (purity ≥99.92%) were weighed respectively, argon was introduced to make the vacuum degree reach 120Pa, and vacuum melting was carried out at 750°C for 10min; then the crucible in the furnace was tilted as a whole, and the molten metal was cast into a preheated graphite mold with a small bottom diameter and a large opening (wall thickness of 20mm, bottom thickness of 10mm, diameter of 15mm, preheating temperature of 230°C), the casting temperature was 710°C, and the casting rate was 23mm / min; finally, the alloy liquid was slowly cooled after being stationary for 15min, and the cooling rate of the slow cooling was 3°C / s to obtain an alloy ingot;

[0094] S2, the alloy ingot in step S1 is first subjected to a two-stage variable temperature homogenization heat treatment at 400°C / 4h and 280°C / 4h, with a vacuum degree of <1×10 -2 Pa, after the treatment is completed, water cooling and air cooling and drying treatment are carried out; lubricating oil is applied to the surface of the alloy ingot, and equal-diameter angular extrusion deformation treatment is carried out, the extrusion angle is 150°, the mold temperature is 480°C, the extrusion temperature is 460°C, and 8 extrusion passes are performed. Annealing treatment is performed between every two passes, the annealing temperature is 420°C, and the time is 10 minutes. After the end, water cooling is carried out to prevent grain growth and retain its deformation structure, and the initial extruded ingot is obtained;

[0095] S3, the initial extruded ingot in step S2 is first subjected to stress relief annealing at a temperature of 280°C and a time of 110 min, and then cooled in the furnace after the stress relief annealing is completed; then warm rolling deformation treatment is performed, the rolling rate is 60 mm / s, the rolling temperature is 400°C, and the rolling is performed for 7 passes, the first rolling reduction is 20%, and the remaining rolling reduction is 10%, and annealing treatment is performed between every two passes, the annealing temperature is 380°C and the time is 15 min, and water quenching treatment is performed immediately after the warm rolling deformation treatment is completed to obtain an intermediate transition rolling ingot;

[0096] S4. The intermediate transition rolled ingot described in step S3 is first polished on both sides by 0.1 mm using 2000# sandpaper in the rolling direction, lubricating oil is applied to the normal contact surface of the polished sample, and then ultrasonic surface rolling treatment is performed. The diameter of the polishing ball is 12 mm, the material of the polishing ball is WC / Co, the rolling ultrasonic frequency is 30 Hz, the ultrasonic amplitude is 8 μm, the feed rate is 40 mm / min, the static pressure load is 350 N, the spindle speed is 200 rpm, and the double-sided rolling is performed 4 times. During the ultrasonic surface rolling treatment, liquid nitrogen spray cooling is performed every 2 minutes to prevent high-temperature oxidation and deterioration of the surface properties of the material, so as to obtain a medical magnesium alloy.

[0097] The corrosion fatigue performance of alloy plates was tested in accordance with GB / T 20120.1-2006 "Corrosion of Metals and Alloys - Corrosion Fatigue Tests Part 1: Cyclic Failure Tests". Under the test conditions of stress ratio of -1 and loading frequency of 1Hz, the corrosion fatigue strength of medical magnesium alloys in a simulated physiological environment was ≥280MPa and the fatigue life was ≥10 5 Second-rate.

[0098] Figure 3 The SEM morphology of the surface film layer of the alloy obtained in Example 3 after being immersed in a simulated body fluid environment at 37±0.5℃ for 7 days. Compared with the SEM cross-sectional morphology of the alloy obtained in Example 1, the cross-sectional morphology obtained in Example 3 is more dense and the surface film layer has less defects. This is because the ultrafine grain structure and high-density grain boundaries obtained by ultrasonic surface rolling can quickly serve as film layer nucleation points, enhance the bonding force between the film layer and the substrate, and enhance the defense capability of the substrate against corrosive solutions.

[0099] Figure 4 This is the SEM microstructure of the medical magnesium alloy prepared in Example 3. Figure 4 It can be seen that the high-density grain boundary structure under the composite deformation process can promote the surface lattice torsion and weaken the basal texture, promote the simultaneous activation and initiation of the basal / non-basal slip system, and thus significantly improve the corrosion fatigue resistance of the medical magnesium alloy, and obtain a medical magnesium alloy with high ultimate strength and excellent corrosion fatigue resistance.

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A medical magnesium alloy, characterized in that: The invention comprises the following chemical components in mass percentage: Er: 1.83-2.10%, Gd: 6.10-8.40%, Ag: 0.15-0.25%, graphene nanosheets GNPs: 0.03-0.25%, Zn: 1.70-3.35%, and the balance is Mg.

2. The method for preparing a medical magnesium alloy according to claim 1, characterized in that: The following steps are involved: S1. According to the mass percentage of chemical components, Mg alloy, Zn alloy, Ag, GNPs sheet material, magnesium-erbium alloy ingot and magnesium-gadolinium master alloy are mixed, vacuum smelted and cast to obtain alloy ingot; S2, performing equal-channel angular extrusion deformation treatment on the alloy ingot in step S1 to obtain an initial extruded ingot; S3, performing warm rolling deformation treatment on the initial extruded ingot in step S2 to obtain an intermediate transition rolled ingot; S4, performing ultrasonic surface rolling treatment on the intermediate transition rolling ingot described in step S3 to obtain a medical magnesium alloy.

3. The preparation method according to claim 2, characterized in that: In step S1, the vacuum melting conditions include: the atmosphere is argon, the vacuum degree is 120-150 Pa, the temperature is 720-750°C, and the time is 10-12 min; in step S1, the casting conditions include: the temperature is 680-710°C, and the casting rate is 20-25 mm / min.

4. The preparation method according to claim 2 or 3, characterized in that: In step S1, a slow cooling treatment is further included after the casting, and the cooling rate of the slow cooling treatment is 1 to 3°C / s.

5. The preparation method according to claim 2, characterized in that: In step S2, the conditions of the equal-channel angular extrusion deformation treatment include: an extrusion angle of 120 to 150°, a mold temperature of 470 to 480°C, an extrusion temperature of 440 to 460°C, and 6 to 8 extrusion passes; annealing treatment is performed between every two passes, the annealing treatment temperature is 390 to 420°C, and the annealing treatment time is 10 to 13 minutes.

6. The preparation method according to claim 2 or 5, characterized in that: In step S2, the alloy ingot is further subjected to a secondary variable temperature homogenization heat treatment before the equal channel angular extrusion deformation treatment; the conditions of the secondary variable temperature homogenization heat treatment include: the temperature of the first stage heat treatment is 320-400°C, the holding time of the first stage heat treatment is 4-6h, the temperature of the second stage heat treatment is 260-280°C, the holding time of the second stage heat treatment is 4-6h, and the vacuum degree is less than 1×10 -2 Pa.

7. The preparation method according to claim 2, characterized in that: In step S3, the conditions of the warm rolling deformation treatment include: a rolling rate of 40 to 60 mm / s, a rolling temperature of 360 to 400°C, 5 to 7 rolling passes, a first rolling reduction of 15 to 20%, and a remaining rolling reduction of ≤8 to 10%; annealing treatment is performed between every two passes, the annealing treatment temperature is 360 to 380°C, and the annealing treatment time is 10 to 15 minutes.

8. The preparation method according to claim 2 or 7, characterized in that: In step S3, the initial extruded ingot is subjected to stress relief annealing before the warm rolling deformation treatment; the stress relief annealing conditions include: a temperature of 250-280° C. and a time of 90-110 min.

9. The preparation method according to claim 2, characterized in that: In step S4, the conditions of the ultrasonic surface rolling treatment include: the diameter of the polishing ball is 8 to 12 mm, the rolling ultrasonic frequency is 20 to 30 Hz, the ultrasonic amplitude is 6 to 8 μm, the feed rate is 20 to 40 mm / min, the static pressure load is 280 to 350 N, the spindle speed is 180 to 200 rpm, and the number of double-sided rolling is 2 to 4 times; during the ultrasonic surface rolling treatment, liquid nitrogen spray cooling is performed every 2 minutes.

10. Use of the medical magnesium alloy according to claim 1 or the medical magnesium alloy prepared by the preparation method according to any one of claims 2 to 9 in the preparation of medical magnesium alloy sheets.